Urinary Bladder Tuberculosis - A Case Report (Faridpur Medical College Journal, 2011)
Genito-urinary tuberculosis is an infrequent but not uncommon condition in countries with high incidence of tuberculosis like Bangladesh. A female patient of 25 years was admitted into Faridpur Medical college Hospital with acute retention of urine with history of haematuria, dysuria, fever and difficulty in urination for about three years. USG revealed few masses in the urinary bladder, later proved by histopathological examination as granulomatous lesion consistent with tuberculosis. Anti-TB treatment was given and the masses were removed surgically. With this treatment recovery of the patient is satisfactory and symptoms are disappearing. The aim of this study to make internist more efficient to diagnose the disease by strong clinical suspicion and relevant laboratory investigation, otherwise such uncommon disease and its complications may endanger life of such patient. DOI: 10.3329/fmcj.v5i2.6826Faridpur Med. Coll. J. 2010;5(2):66-68